Rheumatoid Arthritis and its Relationship with Vitamin D, ESR, and Obesity - Fatima Rashid Mohan; Aya Talib Jawad; Amany Shakeir Jaber (International Journal of Toxins and Toxics, 2024)
Recent years have seen a rise in the prevalence of rheumatoid arthritis (RA), a disease marked by the destruction of articular cartilage and ankylosis of the joints, as well as other complications such as diffuse lung inflammation, sclera, pleura, pericardium, and nodular lesions, which are also common in subcutaneous tissue. Reviewing RA symptoms, diagnosis, treatment, and associations with vitamin D, ESR, and obesity was the aim of the study. Even though erythrocyte sedimentation rate (ESR) is not an etiologic diagnosis, it can be regularly utilized for inflammatory surveillance in individuals with RA. It is brought about by the straightforward, useful, affordable, point-of-care examination method known as ESR, which also has substantial clinical significance. The majority of earlier research has shown that vitamin D insufficiency is the cause of rheumatoid arthritis. Flares and remissions are features of rheumatoid arthritis (RA), an inflammatory illness that is marked by pain. Diffuse musculoskeletal discomfort is also known to be linked to vitamin D insufficiency. Excess visceral adiposity is linked to higher levels of systemic cytokines, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR). Obesity is an inflammatory state. This finding has given rise to the theory that obesity plays a role in the onset, progression, and maintenance of systemic inflammatory diseases, such as inflammatory arthritis. This theory is supported by the finding that psoriasis, psoriatic arthritis, and metabolic obesity appear to be strongly correlated, and that those who lose weight following bariatric surgery have a significantly lower chance of developing psoriasis. We found that patients with RA who were obese had a higher likelihood of having elevated inflammatory markers after examining other studies.
Keywords: C-reactive protein; ESR; Vit D; and RA; obesity